Update in primary pulmonary lymphomas. Issue 4 (July 2015) - Cardenas-Garcia, Jose; Talwar, Arunabh; Shah, Rakesh; Fein, Alan
Abstract : Purpose of review: Despite the fact that primary pulmonary lymphoma (PPL) is a rare lung tumour, significant advances addressing clinical features, histological diagnosis, prognostic criteria and therapeutic management of this disease have been made within the past decade. Recent findings: Monoclonality and phenotyping of alveolar lymphocytes are suggestive of mucosa-associated lymphoid tissue (MALT). Detection of MALT-1 gene rearrangements in bronchoalveolar fluid cells using fluorescence in-situ hybridization techniques helps to confirm the diagnosis of MALT PPL. Fine needle aspiration-computed tomography guided biopsies as well as transbronchial/cryobiopsies provide adequate tissue material for histological evaluation. Recent publications also provide a better appreciation of newer chemotherapeutic approaches, including fludarabine and mitoxantrone with or without ritubximab for the treatment of MALT, as well as complete surgical resection if local disease is present. Prognostic factors influencing survival and optimal therapy for MALT have not been well defined, but the use of tumour microvascular density appears promising. Summary: This review outlines the implications of recent findings for clinical practice and research progress of PPL. Larger, multicentre and well designed studies are imperative to optimize the current diagnostic and therapeutic approach for this disease.